Perancangan Sistem Informasi Ujian Online Menggunakan Metode Extreme Programming - Juniadi Yudhistira (PT. Tech Cart Press, 2024)
Problems that often occur related to school exams include the risk of cheating in exams, the problem of cheating in exams is a significant challenge in the education system. Cheating can take many forms, from cheating, communicating with fellow students during exams, to using tools that are not allowed. This can be detrimental to students studying hard and create inequities in assessment. The online exam information system is a digital platform that allows the implementation of online exams using information and communication technology. Through this system, students can access and take exams from anywhere with an internet connection, reducing geographical and time limitations. The system also facilitates efficient examination management for educational institutions. In the test results black box testing shows results obtained by 100% for the online exam system, each feature tested has passed all planned test scenarios successfully. These results provide confidence that the online examination system has been comprehensively tested and is ready to be used with high quality, increasing user confidence in using the platform for evaluation and assessment purposes.